Methods for evaluating alternative types of multi-purpose tactical aircraft for the renewal of the tactical aviation fleet of the air force of the armed forces of Ukraine - Leontiev, Oleksii; Naumenko , Maryna (Social Development and Security, 2021)
The article presents a methodology for assessing the main combat and military-economic indicators of the types of multipurpose tactical aircraft, which can constitute many alternative options for updating the tactical aviation fleet of the Air Force of the Armed Forces of Ukraine. The methodology is based on a systematic consideration of the relationship between the quality indicators of multipurpose tactical aircraft, financial price indicators for the purchase of alternative types of tactical aircraft and predicted estimates of financial costs at the stage of their operation. A feature of the proposed methodology is the ability to operate with quantitative estimates of these indicators. As indicators of quality, it is proposed to take the coefficients of the combat potentials of alternative types of tactical aircraft when they perform tasks to counter an air enemy and when they perform tasks of destroying ground targets. It is proposed to evaluate the values of these coefficients using quasimetric models of the fighter and strike properties of a multipurpose tactical fighter, which are functional dependences of these indicators on the values of the tactical and technical characteristics of the aircraft. It is proposed to estimate the price of one aircraft in possible purchase contracts by using a mathematical model of the cost of one multipurpose tactical aircraft, which is developed and mass-produced for the own needs of the armed forces of the manufacturing country, represented as a functional dependence of this price on values of the coefficients of the combat potentials of the aircraft. After that, the price for aircraft purchased by import is adjusted taking into account export charges, which are determined according to statistics. It is proposed to estimate the financial costs of operation and all-round support for the use of tactical aircraft and the corresponding infrastructure available for the purchase, relying on the concept of a typical life cycle of military aviation equipment and a typical distribution of its cost over the main stages and stages, which are the main tool for obtaining predicted cost values stages of the life cycle of samples of military aircraft.